Properties of Cohereditary Comodule - Hanni Garminia; Pudji Astuti; Irawati Irawati (Institut Teknologi Bandung, 2007)
Let R be a commutative ring and C be an R-coalgebra which, as an R-module, is locally projective. This article describes some properties of a cohereditary C-comodule. The properties are derived by exploiting the closed connection between the C*-comodule category and the full subcategory of the C*-module category consisting of all C*-subgenerated C*-modules, where C* is the dual algebra of C.